ANALYSIS OF REFLECTIVE GAME OF AGENTS IN TELECOMMUNICATIONS MARKET FOR A CASE OF TWO REFLECTIVE AGENTS - I. A. Biryukova; M. I. Geras’kin (Russian Journal of Economics and Law)
Objective: comparative analysis of reflexive and non-reflexive strategies of market agents’ behavior in accordance withStackelberg equilibrium.Methods: game theory, economic and mathematical modeling.Results: modeling of information equilibria of the Russian telecommunications market is carried out. In the game of three oligopolists on arbitrary ranks of strategic reflection of two of them, the possible variants of equilibria are analyzed; the solution of all available variants of equilibria on arbitrary ranks of reflection at linear functions of demand and expenses is received. Modeling of information equilibria of the Russian telecommunications market showed possible strategies to improve the agents’ market positions.Scientific novelty: the equilibrium in the market of oligopoly with three agents is considered, two of which reflect, and the third acts in accordance with their ideas. The reflexive behavior of the oligopoly market agents leads to a significant shift in the market equilibrium in comparison with non-reflexive behavior, while the strategy of the non-reflexive agent is ineffective in all cases, since its market share decreases with an increase in the reflection rank.Practical significance: the obtained informational equilibria can be used for comparison with the structure of the Russian telecommunications market to determine the type of the companies’ reflexive behavior.